X-linked Thrombocytopenia with Normal Wiskott-Aldrich Syndrome Protein Expression in Lymphocytes and a Novel Wiskott-Aldrich Syndrome Protein Gene Variant: A Case Report and Brief Review of the Literature - Serena Hamanaka, MD; Toru Uchiyama, MD, PhD; Tadashi Kaname, MD, PhD; Motohiro Matsui, MD; Hiroshi Yoshihashi, MD; Atsushi Makimoto, MD, PhD; Yuki Yuza, MD; Akira Ishiguro, MD (Journal of Pediatrics: Clinical Practice)
We present a case of X-linked thrombocytopenia (XLT) with a novel WAS gene variant expressing a normal amount of Wiskott-Aldrich syndrome protein (WASp) in lymphocytes. XLT usually decreases WASp expression not only in platelets, but also in lymphocytes. However, there were cases, such as the present one, in which WASp was expressed normally in lymphocytes and absent only in platelets. Our finding suggests that it is of greater diagnostic sensitivity to perform an expression analysis of WASp in both platelets and lymphocytes when XLT is suspected.